Gender and migration in Italy: a multilayered perspective - Olivito, Elisa (Law and migration, 2016)
Migrant women and social mobility in a historical perspective -- Self-determination, family, and welfare -- Culture, patriarchy, and religion -- Citizenship and second-generation migrant women